Visualization of Science Literacy in Learning Based on STEM at Natural Schools, Bengkulu Indonesia - Widya Kartika Sari; Dodo Sutardi; Bentar Priyopradono (Universitas Prof. Dr. Hazairin, S.H, 2022)
One of the problems of education in Indonesia today is the low literacy of mathematics, science and reading. STEM (Science Technology Engineering Math) education is an effort made by almost all countries to improve scientific, technological, and mathematical literacy. Indonesia developed the 2013 curriculum to improve literacy. Several research results on STEM education in Indonesia conclude that STEM education has been well understood by most teachers in Indonesia. However, in the implementation of learning, not many have implemented it. This paper will visualize the implementation of STEM education in improving students' literacy skills, and help achieve the Alam Bengkulu school's vision,